Size effects in thin n-PbTe films - Men'shikova, S.I.; Rogacheva, E.I.; Sipatov, A.Yu.; Zubarev, Ye.N. (Functional Materials, 2014)
The effect of the film thickness d on the Seebeck coefficient S, the Hall coefficient RH, electrical conductivity σ, charge carrier mobility μH and thermoelectric power factor S²σ of thin films (d = 7-235 nm) prepared by thermal evaporation of n-type PbTe polycrystals doped with InTe in vacuum onto (001)KCl substrates was investigated. It was established that at d ≈ 20 nm, an inversion of the conductivity type (p → n) occurs, which is attributed to a change in the thermodynamic equilibrium conditions in films as compared with bulk crystals and\or to partial re-evaporation of In atoms. In the thickness range d < 20 nm, extrema in the d-dependences of the properties are detected at d ≈ 13 nm, and at d > 20 nm, the thickness dependences of the properties exhibit an oscillatory behavior with the period Δ d ≈ 12 nm. The observed oscillatory character of the thickness dependences of the kinetic coefficients is attributed to the manifestation of quantum size effects. The theoretical S(d) dependence calculated in the approximation of size quantization taking into account d-dependences of the Fermi energy and a number of subbands is in good agreement with the experimental one with regard to the oscillation period.